ANALISIS RISIKO PRODUKSI PADA UASHATANI PADI SAWAH DI DESA SUKOREJO KECAMATAN SUKOREJO KABUPATEN PONOROGO - haryadin haryadin; Sri Hindarti (Program Studi Agribisnis, 2019)
AbstractThis study aims to analyze the risk of wetland rice production between the land area of <0.5 hectares with a land area of ≥ 0.5 hectares, knowing what factors influence the risk of rice production and analyzing farmers' preferences in facing the risk of rice production. This research was determined by purposive sampling in Sukorejo Village, Sukorejo District, Ponorogo Regency. The sampling method is used by cluster sampling, so that the samples obtained are 50 wetland rice farmers from 512 scattered populations into four hamlets. The analytical methods used are, Variance Coefficient (CV), cobb-Douglas production function analysis, variance analysis of production and Observed Economic Behavior (OEB) analysis. The results showed the level of risk of wetland rice production with a land area of <0.5 hectares greater than the land area of ≥ 0.5 hectares. Factors that have a significant effect on the risk of wetland rice production namely, seeds, labor and pesticide. Farmer's preference for inputs that affect production risk, seed (risk averse), labor (risk taker) and pesticide (risk averse).Keyword: Risk, Production, wetland rice